Additive manufacturing of architected catalytic ceramic substrates based on triply periodic minimal surfaces - Al‐Ketan, Oraib; Pelanconi, Marco; Ortona, Alberto; Abu Al‐Rub, Rashid K. (Journal of the American Ceramic Society, 2019)
The exhibited geometry of catalytic substrates can have a significant influence on the chemical activity and efficiency. Controlling their geometry can be challenging using the traditional techniques. In this work, we propose new and novel catalytic substrates with architected and controllable topologies based on the minimal surfaces framework. A novel design approach and an additive manufacturing (AM) technique were proposed to manufacture the catalytic substrates using ceramic materials. After 3D printing, their mechanical and flow properties were investigated experimentally. An elastic‐plastic‐damage coupled model was employed to investigate the underlying deformation mechanism of the investigated substrates. Results showed that the CLP substrate exhibited the highest mechanical properties as well as the least pressure drop among the tested substrates. Also, numerical simulations showed that the strut‐based substrates exhibit stress localization which leads to faster failure, while stress is distributed more homogeneously in the sheet‐based substrates. While the model showed to have a good agreement in the experimental and simulation stress‐strain responses, the damage mechanism was not fully captured by the numerical simulations. This was attributed mainly to the process‐induced defects in the form of microcracks and microvoids that can alter the nature of deformation and damage.